Epidemiologia da leishmaniose visceral canina em Parauapebas, Pará, Brasil. - Sá, Gustavo José de Lima de (2020)
The Visceral Leishmaniasis (VL) or calaza is a zoonosis caused by protozoa intracellulars from Trypanosomatidae, description Leishmania. In Pará state it was infromad 580 cases of human visceral leishmaniasis in 2017 and occording to the last quiquennial dates, the VL is a harn that is presente in 117 of 144 cities in Pará state and 19 from this cities are cosedered of intnse transmission. The fore the purpose of this research was determinate apidemiologic character of CVL in Parauapebas, located in southeast region from the state. To compound the sample, the dogs were included for convenience, admiting animals from any race, gender, size or live place, age iqual or superior 4 month. The samples were realized in loco by domiciliar visits or when the aniaml was took to the data collection places in a neighborhood were the city hall promoted on action by Helth Sevice Departamento of city to the control VL. The serum sample of 389 dogs were analyzed by immunochromatographic (DPP®) test. The lymph nodes aspirate was colected of puncture, colored in Panótico® and analyzede in optic microscopy. A sheet of enviromental question was filled out fro each animal and the variable used to test the combination. In 41 neighborhood of Parauapebas city was diagnosticed positive dogs to VL in at least a realized test. The sorophrevalence found it was 32,6% (28,1 – 37,4) considering the positive in both test concurrenthy. Introduced like associetted factos to soropositivity of VL, animals with no breed definition (OR= 3,119, P= 0,000) free access to the streets (OR= 1,956, P= 0,019), stay out of residence among 6:00 p.m to 10:OO p.m (OR= 3,129, P= 0,001), dermatites generalized (OR= 4,711, P= 0,000), periocular dermatitis (OR= 6,518, P= P= 0,006), splenomegaly (OR= 7,347, P= 0,042), hapatomegaly (OR= 8,812, P= 0,019), lymphadenomegaly (OR= 3,796, P= 0,002) and onychogryphosis (OR= 5,718, P= 0,013). The CVL is distributed in a large way in Parauapebas city, with high predominance confirmed by straight parasitologic exams. The desiase sorophrevalence is really high among the dogs, using the fast test, it’s recommended to do a confirmatory test to consider the positive. The result got in the studies indicate that is possible that occur a raise in the incidence of VL in Humans in Parauapebas city, if it doesn’t have.